Ulule, du courtage à la structuration des pratiques de création dans l’édition, la musique et l’audiovisuel - Manuel DUPUY-SALLE; Laurie SCHMITT (Tic & Société)
This article focuses on crowdfunding platforms as socio-technical devices that organize connections between different actors in the cultural industries. As additional “intermediaries”, these platforms help structure creative practices in the cultural field, for the actors of content that capture them. We examine how the use of crowdfunding by cultural industry players is part of an ongoing trend within various sectors. We then consider the mutations that underlie this phenomenon: crowdfunding combines old and new practices. Finally, we discuss how crowdfunding is mobilized differently according to sectors, carriers or platforms. Our study is based on the analysis of 472 projects on the Ulule platform between 2016 and 2017 and ten semi-structured interviews with project sponsors and the CEO of Ulule.